PENINGKATAN MUTU PENDIDIKAN MELALUI PARADIGMA BARU - Idawati; Fiqra Amaliah ZR; Intan Junaeda; Sitti Rumaisha (STKIP Subang, 2025)
The quality of education in Indonesia continues to face various challenges despite numerous improvement efforts and policy reforms. This study aims to analyze the concept of educational quality, the factors influencing it, the differences between the traditional and new educational paradigms, as well as the challenges and solutions in its implementation. The method used is a literature review by analyzing theoretical sources and educational policy regulations. The findings indicate that educational quality encompasses interconnected aspects of inputs, processes, outputs, and outcomes. The shift in educational paradigms from centralization to decentralization and from teacher-centered to student-centered learning creates opportunities to improve innovation in teaching and school management. However, implementation in the field still encounters obstacles, particularly related to teacher competence, infrastructure limitations, and insufficient support from local governments. Therefore, enhancing teacher professionalism, strengthening school-based management, increasing policy support at the regional level, and utilizing educational technology are essential to sustain improvements in educational quality. Keywords: educational quality, new paradigm, decentralization, school management, 21st-century learning.